Psicología rural: retos y reflexiones en torno a la psicología en contexto rural. - Camargo Barrero, José Antonio; Mayorga González, José Miguel; Castañeda Polanco, Juan Gabriel (Corporación Universitaria Minuto de Dios, 2021)
El presente libro es un aporte derivado de investigación, que tiene como objetivo dar a conocer algunas particularidades de la psicología en contexto rural, como lo son las funciones del psicólogo rural, las competencias que debe desarrollar y los principales nichos de investigación que se han trabajado en los últimos años en torno a diversas temáticas, haciendo énfasis en el suicidio como tema de salud mental.

The work in rural context has some particularities of rurality that in some cases have not been taken sufficiently into account in the work of some professionals in disciplines such as psychology, so this book aims, based on a documentary research, to present from a theoretical-reflexive perspective, what is usually called and be the work of rural psychology, starting with a first part of the definition of rurality and professional skills that should develop a psychologist working in rural areas; then, to show some of the main investigations that have been carried out in the last years in this field and to emphasize the problem of suicide; ending with a second part in the form of reflection from the logotherapy for life and the conurbation, of the phenomenon of the rural-urbanity.
Keywords: Ruralidad; Psicología rural; Contexto rural; Sujeto rural; Suicidio; 307.7; Rurality; Rural psychology; Dynamics relate in rural context; Rural subject; Suicide; Sociología rural; Población rural - Aspectos psicológicos; Condiciones rurales - Estudios de casos; Psicología de la comunidad